1986
DOI: 10.1007/bf00422884
|View full text |Cite
|
Sign up to set email alerts
|

Beta-endorphin and ACTH levels in peripheral blood during and after aerobic and anaerobic exercise

Abstract: Beta-endorphin (beta-End) and adrenocorticotrophic hormone (ACTH) were determined in the peripheral blood of 14 human volunteers exercising on a bicycle ergometer. After 1 h of submaximal work below anaerobic threshold (AT), defined as the 4 mmol X l-1 lactic acid level in arteriolar blood (Kindermann 1979; Mader 1980), beta-End and ACTH levels did not change from control conditions. Eleven of the same 14 subjects performed an uninterrupted graded exercise test on the same bicycle ergometer until exhaustion. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1
5

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(26 citation statements)
references
References 11 publications
1
19
1
5
Order By: Relevance
“…It has been suggested that neuroendocrine and sympathoadrenal responses to exercise are more closely related to relative exercise intensity (Kjaer et al 1988) or blood lactate concentrations (De Meirleir et al 1986) than to the absolute work load per se. In our study, lactate concentrations after the training set and set velocities were similar in all sessions; thus, as has been suggested by Buono et al (1987), other factors, such as a lesser extent of disturbance in intracellular homeostasis sensed by peripheral chemorecptors, and/or an increased sensivity to ACTH control by cortisol, should be taken into account to explain the attenuated response of ACTH.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that neuroendocrine and sympathoadrenal responses to exercise are more closely related to relative exercise intensity (Kjaer et al 1988) or blood lactate concentrations (De Meirleir et al 1986) than to the absolute work load per se. In our study, lactate concentrations after the training set and set velocities were similar in all sessions; thus, as has been suggested by Buono et al (1987), other factors, such as a lesser extent of disturbance in intracellular homeostasis sensed by peripheral chemorecptors, and/or an increased sensivity to ACTH control by cortisol, should be taken into account to explain the attenuated response of ACTH.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy, exercise-trained volunteers, strenuous workout on a bicycle ergometer increased E levels threefold and showed positive correlation with exercise capacity (Schwarz and Kindermann 1989). ACTH level and E levels increase concurrently-anaerobosis is thought to play an important role in this phenomenon (de Meirleir et al 1986). In a study conducted on marathon runners, ten subjects were tested after completing the 42.195-km distance, and additional Wve were tested following submaximal exercise testing (50% VO 2 max) on a bicycle ergometer.…”
Section: Exercise and E Levelsmentioning
confidence: 98%
“…Similarly, production of β‐endorphins, adrenocorticotropic hormone, and endogenous opioid peptide neurotransmitters with analgesic properties serve to reduce arousal at the neuronal level . Research examining peripheral blood levels has found elevations in β‐endorphins and adrenocorticotropic hormones after various types of exercise and associated reductions in anxiety . Finally, exercise down‐regulates the hypothalamic–pituitary–adrenal axis and sympathetic nervous system—systems that tend to become dysregulated as a function of chronic stress—thereby normalizing release of cortisol and catecholamines and reducing arousal and distress (for reviews see).…”
Section: Potential Mechanismsmentioning
confidence: 99%